In vitro cytotoxicity assay of D-limonene niosomes: an efficient nano-carrier for enhancing solubility of plant-extracted agents - Mohammad Reza Hajizadeh; Haniyeh Maleki; Mahmood Barani; Mohammad Ali Fahmidehkar; Mehdi Mahmoodi; Masoud Torkzadeh-Mahani (Wolters Kluwer Medknow Publications, 2019)
The low solubility of the plant-extracted agent like D-limonene in cancer therapy is a critical problem. In this study, we prepared D-limonene-loaded niosomes (D-limonene/Nio) for cancer therapy through in vitro cytotoxicity assay of HepG2, MCF-7, and A549 cell lines. The niosomal formulation was prepared by film hydration technique with Span® 40: Tween® 40: cholesterol (35:35:30 molar ratio) and characterized for vesicle distribution size, morphology, entrapment efficiency (EE%), and in vitro release behaviour. The obtained niosomes showed a nanometric size and spherical morphology with EE% about 87 ± 1.8%. Remarkably prolonged release of D-limonene from niosomes compared to free D-limonene observed. The loaded formulation showed significantly enhanced cytotoxic activity with all three cancer cell lines (HepG2, Macf-7 and A549) at the concentration of 20 μM. These results indicated that niosome loaded with phytochemicals can be a promising nano-carrier for cancer therapy applications